Matching labor's share in a search and matching model - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2011)
In the United States, labor's share of income falls after a positive disturbance to productivity growth or inflation, and it remains low for some time. Previous researchers have argued that the negative relationship between productivity growth and labor's share is puzzling. I argue otherwise. A search and matching model with infrequently bargained nominal wages would predict the observed behavior of labor's share after a productivity disturbance, and it also predicts the observed behavior of labor's share after an inflationary disturbance. Wages at the macroeconomic level seem to be sticky in a way which is consistent with microeconomic evidence; much of the ongoing discussion about the real effects of sticky wages seems to be well-motivated, while sticky price models fail to match the data.
Keywords: E24; E25; J23; J31; 330; sticky wages; sticky prices; staggered Nash bargaining; inflation; productivity; search and matching; labor share